Effects of Soil Moisture, NPK Fertilizers and Varieties on Grain Growth of Barley (Hordeum vulgare L.) - Mollah, MSI; Rashid, MH; Hossain, MS; Khalekuzzaman, M (Progressive Agriculture, 2013)
The experiments are conducted in the experimental field of the Department of Botany, Rajshahi University during the winter season of 2005-2006 to study the effects of soil moisture and NPK fertilizers on grain growth of four barley varieties (Hordeum vulgare L.) following split-split plot design. The highest grain growth parameters like, spikelet number, spike dry weight, grain number and grain dry weight, spike relative growth rate and grain relative growth rate were observed in the I2 treatment at different days after anthesis. F3 treatment produced the highest spikelet number, spike dry weight, grain number, grain dry weight, spike relative growth rate and grain relative growth rate but the control produced the lowest values. BHL-3 produced higher spikelet number and grain relative growth rate. BL-1 produced higher spike dry weight, grain number, grain dry weight and spike relative growth rate. DOI: http://dx.doi.org/10.3329/pa.v19i1.16985 Progress. Agric. 19(1): 13 - 21, 2008